Qualitative Evaluation of Antibiotics Use with Gyssens Method in Sepsis Patients at Fatmawati Central General Hospital Jakarta - Masyrifah, Mas; Andrajati, Retnosari; Yudhorini, Linda Triana (Pharmaceutical Sciences and Research, 2022)
Sepsis still becomes a major health problem worldwide, with a fairly high mortality rate ranging from 20 to 50%. Antibiotic therapy with rational use can reduce the mortality rate. In contrast, the irrational use of antibiotic therapy will increase the occurrence of resistance, which impacts the increase of morbidity, mortality, and health costs. The objective of this study was to evaluate the quality in the use of antibiotics using the Gyssens method in patients with sepsis. This study was an observational study with a cross-sectional method conducted at Fatmawati Central General Hospital Jakarta from January to December 2020. The research subjects were 110 patients with sepsis who met the inclusion criteria. In this study, 49.09% of patients used rational antibiotics and 50.91% of patients used irrational antibiotics that were found in category VI (0.91%), V (17.28%), IVa (3.63%), IVb (0.91%), IVc (0.91%), IIIa (3.63%), IIIb (20%), IIa (0.91%), and IIb (2.73%). The duration of antibiotic therapy was the only factor that affected the quality of antibiotic use (p = 0.012). There was no difference in mortality between patients with rational and irrational use of antibiotics (p = 0.333, OR = 1.654, 95% CI 0.714-3.829). However, after adjusting for the duration of therapy, irrational use of antibiotics significantly affected mortality (p = 0.017, OR = 3.5, 95% CI 1.255-9.761). In conclusion, the antibiotic use in half of the sepsis patients were irrational. Since irrational use was associated with mortality, efforts need to be taken to improve the quality of antibiotic use.